The importance of clonal selection of grapevine and the role of selected clones in production of healthy propagating stocks - Hajdu, E.; Korac, N.; Cindric, P.; Ivanisevic, D.; Medic, M. (International Journal of Horticultural Science, 2011)
Genetical alterations and phytosanitary status promote the variability and modify the appearance of vine. Old vine varieties in old vineyards are highly variable and well adapted to selection. Clonal selektion is based on a visual performance: valuable individuals (clones) are picked out according to visible symptoms or characters. The genetical stability of clones is proved by testing the vegetatively propagated progenies on the basis of morphological and molekular (SSR, AFLP, SMPL, RAPD) markes. Authors take great care of the visual phytosanitary selection as part of the clonal selection being the oreliminary step to develop pathogen-free propagation stocks. In Serbia (Vojvodina) the selection breeding has been carried on for several decades resulted in comparative clone trials with home and imported clones of Welsch Riesling, Chardonnay, Pinot gris, White Riesling. Among the clones of home selection SK.54 Welsch Riesling clone is the most valuable. Its clearing from pathogene is being carried on in an interregional IPA programme (HUSRB/0901/214/123) in Kecskemét. In Kecskemét, the centre of the Hungarian Danube vine region 5 vine clones have been registered (Cegléd szépe K.73, Irsai Olivér K.11, Kövidinka K.8, Hárslevelû K.9, Pannónia kincse K.56). Besides them 18 virus-tested clones have also been qualified.Works aiming at their complete exemption are going on in order to obtain clones free of propagation wood-borne diseases.